An analysis of the effect of staircase intermediate landing floor on the evacuation time - Mohamad Yatim, Yahya (Faculty of Built Environment, UTM, 2008)
Escape routes in high-rise residential buildings are an important element for emergency escape. Escape stairs are normally designed with intermediate landing floors to connect two staircases between the floor levels in high-rise buildings. This paper discusses an analysis of the effect of this intermediate landing floor on the total evacuation time during evacuation in emergency situation e.g. fire emergency Analysis was done by comparing two different staircases width i.e. 914mm designed with and without intermediate landing floors and 1524mm designed with and without intermediate landing floors as well. Evacuation simulation software i.e. SIMULEX was used to simulate a number of people evacuating the predesigned floor models with the different staircase specifications. Total evacuation time recorded from those simulation processes are then compared with the time different taken by the same number of people evacuating the models. It is found that there was an effect on the total evacuation time for the staircase designed with and without intermediate landing floors. The simulation suggested that people will take 15% to 24% longer to evacuate the building if staircase was designed with intermediate landing floors.